2023
DOI: 10.1038/s41598-023-35790-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone scan index (BSI) scoring by using bone scintigraphy and circulating tumor cells (CTCs): predictive factors for enzalutamide effectiveness in patients with castration-resistant prostate cancer and bone metastases

Abstract: Reports of Bone Scan Index (BSI) calculations as imaging biomarkers to predict survival in patients with metastatic castration-resistant prostate cancer (mCRPC) have been mainly from retrospective studies. To evaluate the effectiveness of enzalutamide (ENZ) in Japanese patients with mCRPC and bone metastases using BSI (bone scintigraphy) and circulating tumor cell (CTC) analysis. Prospective, single-arm study at Juntendo University affiliated hospitals, Japan. Patients were administered 160 mg ENZ daily, with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…In our previous study, we demonstrated the efficacy of ENZ in treating mCRPC with bone metastases and showed that the presence or absence of CTCs at baseline correlated with the prolongation of PFS by ENZ treatment [10]. In this study, by analyzing a subgroup from the previous study, we first demonstrated that the absence of CTC detection at baseline might contribute to prolonged OS (Figure 2) and showed the efficacy of chronological analyses of CTC in 43 patients with mCRPC.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In our previous study, we demonstrated the efficacy of ENZ in treating mCRPC with bone metastases and showed that the presence or absence of CTCs at baseline correlated with the prolongation of PFS by ENZ treatment [10]. In this study, by analyzing a subgroup from the previous study, we first demonstrated that the absence of CTC detection at baseline might contribute to prolonged OS (Figure 2) and showed the efficacy of chronological analyses of CTC in 43 patients with mCRPC.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we conducted this study to evaluate the usefulness of CTC analysis in the clinical setting of mCRPC. In a previous study conducted at our facilities and affiliated hospitals, we analyzed PFS in mCRPC patients with bone metastases treated with ENZ and demonstrated that a negative CTC status at baseline before ENZ treatment was a significant predictor for ENZ efficacy [10]. It has already been reported that chronological monitoring of CTCs is very effective for evaluating possible treatments and their efficacy in mCRPC [15][16][17].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…For PC cells, PSA and FGF2 are target proteins for identification [ 113 ]. Another CTC biomarker under clinical investigation is AR-V7 [ 114 ].…”
Section: Biomarkers Of Liquid Biopsy: New Edge Technology For Pc Pati...mentioning
confidence: 99%